Vertical scar versus the inverted-T scar reduction mammaplasty: A 10-year follow-up - Bouwer, Lesley R.; van der Biezen, Jan Jaap; Spronk, Cees A.; van der Lei, Berend (Journal of plastic, reconstructive & aesthetic surgery, 2012)
A retrospective study was undertaken to evaluate whether the initial outcome of two types of reduction mammaplasty techniques (vertical scar reduction mammaplasty vs. the inverted-T scar reduction mammaplasty) remains stable in the long term: Sixty-nine patients who had undergone breast reduction surgery in the period 1997–2000 at the Department of Reconstructive Plastic Surgery at the Medical Center of Leeuwarden were willing and able to participate in this study. A structured questionnaire was used to assess the degree of patient satisfaction. For subjective evaluation, the Strasser Grading System on photographs at the 3 months after surgery and after long-term follow-up (10 years) was used. The median general appreciation mark for the entire surgical procedure given by patients was 8 (1–10) on a scale from 1 to 10. Forty-six of the 69 patients could be scored according to Strasser: at 3 months in 17 patients (37%) the result was ‘good’, in 21 patients (46%) ‘mediocre’ and in eight patients (17%) ‘poor’. After 10 years, in 37 of the patients (80%) the result was ‘good’, in six patients (13%) ‘mediocre’ and in three patients (7%) ‘poor’. At 3 months, there was a higher incidence of bottoming out in the vertical scar group (one on two patients) as compared to the inverted-T scar group (one on 10 patients); however, at the 10-years follow-up bottoming out was 50% in the inverted-T scar group and 20% in the vertical scar group. Despite bottoming out, in both the vertical scar reduction mammaplasty technique and the inverted-T scar reduction mammaplasty technique, high patient satisfaction rates are achieved that remains for years.